Managing catch of marine megafauna: Guidelines for setting limit reference points. (November 2015) - Curtis, K. Alexandra; Moore, Jeffrey E.; Boyd, Charlotte; Dillingham, Peter W.; Lewison, Rebecca L.; Taylor, Barbara L.; James, Kelsey C.
Abstract: Limit reference points (LRPs) for catch, which correspond to thresholds to undesirable population or ecosystem states, offer a consistent, objective approach to management evaluation and prioritization across fisheries, species, and jurisdictions. LRPs have been applied successfully to manage catch of some marine megafauna (elasmobranchs, marine reptiles, seabirds, and marine mammals) in some jurisdictions, such as the use of Potential Biological Removal (PBR) to manage incidental mortality of marine mammals under the U.S. Marine Mammal Protection Act. However, implementation of ecosystem-based management is still in its infancy globally, and LRPs have not yet been widely adopted for marine megafauna, particularly for incidental catch. Here, guidelines are proposed for estimating catch LRPs for marine megafauna, with particular attention to resolving common technical and political challenges, including (1) identifying management units, population thresholds, and risk tolerances that align with common conservation goals and best practices, (2) choosing catch LRP estimators, (3) estimating input parameters such as abundance and productivity, (4) handling uncertainty, and (5) dealing with mismatches between management jurisdictions and population boundaries. The problem of cumulative impacts across sectors is briefly addressed. These guidelines, grounded in marine policy, science, precedent, and lessons learned, should facilitate wider application of catch LRPs in evaluation and management of fisheries impacts on marine megafauna, in support of global commitments to conserve biodiversity and manage fisheries responsibly. Highlights: Biological catch LRPs are effective for managing catch of marine megafauna. Guidelines for estimating catch LRPs for marine megafauna are proposed. Default biological thresholds, to which catch LRPs correspond, are identified. Catch LRPs for populations that span management jurisdictions are addressed.